Impacto das fake news nos negócios internacionais - Longo, Juliano (My University, 2020)
The present study approaches the impact of fake news on International Trade and it aims to analyze the impacts of fake news in the perception of international trade professionals. Therefore, international trade and fake news were conceptualized, the dimensions of fake news were identified, the experiences of companies with fake news in their international business were reported, and measures were proposed to minimize their impact. The present study consists in research of a descriptive and a qualitative approach was adopted, with a collection of information data from secondary sources. After analyzing the data, it was possible to conclude that fake news is still not as relevant to professionals working in the field of International Trade, even thought they have been showing to drastically affect the world in several sectors. [resumo fornecido pelo autor]
Este estudo aborda o impacto das fake news no Comércio Internacional e tem como objetivo analisar os impactos das fake news na percepção dos profissionais de Comércio Internacional. Para tanto, foram conceituados comércio internacional e fake news, identificadas as dimensões das fake news, relatadas as experiência das empresas com as fake news em seus negócios internacionais e foram propostas medidas para minimizar seu impacto. O presente estudo consiste em pesquisa de caráter descritivo e foi adotada uma abordagem qualitativa, sendo feita uma coleta de dados de informações em fontes secundárias. Após a análise dos dados, foi possível concluir que as fake news ainda não são tão relevantes aos profissionais que trabalham na área do Comércio Internacional por mais que elas vêm demonstrando afetar drasticamente o mundo em diversos setores. [resumo fornecido pelo autor]
Keywords: Comércio internacional; Fake news